Analysis of Dominant Number Values Weed Population in Paddy Rice Cultivation (Oryza sativa, L.) in Koya Village, Minahasa, North Sulawesi - Kasim, Yuriko; Lihiang, Anatje; Gedoan, Sukmarayu; Tanor, Meity; Yalindua, Aser; Sumampouw, Herry (Universitas Negeri Manado, 2024)
Paddy rice is the main food crop in Indonesia because rice is the primary food source of the Indonesian people. However, it faces obstacles caused, among others, by the presence of nuisance plants, namely weeds, that can reduce the quantity and quality of harvest or production. This study examines the value of the dominant Number of weed populations in rice field cultivation. The research method used was weed observation with analysis of the chief number value, using the square of a sample plot measuring 50 cm x 50 cm, randomly placed on the experimental land. The dominant number value analysis was carried out four times at the beginning of the study as an initial vegetation analysis, 21 DAP observations, 45 DAP observations, and 60 DAP observations. The results showed that the weed species with the highest Dominant Number Value at initial words in paddy fields were Paspalum disticum, Fibristylis litoralis, Marsilea crenata, Cyperus iria, and Ludwigia octovalvis; weed species with the highest Dominant Number Value at 21 DAP observations were P. disticum, Echinochloa crusgalli, F. litoralis, M. crenata, and Leersia hexandra; The weed species with the highest Dominant Number Value at 45 DAP observations were P. disticum, F. litoralis, C. iria, E. crusgalli, and Leersia hexandra and the weed species with the highest Dominant Number Values at 60 DAP observations were E. crusgalli, P. disticum, F. litoralis, Scirpus juncoides, and S. juncoides